Economic Growth of West African Countries and the Validity of Wagner’s Law: A Panel Analysis - Benedict, Udo, Aniefiok; Efefiom, Effiong, Charles; Ochagu, Ogar, Ohiama (Asian Journal of Economics and Empirical Research, 2016)
The volume of public expenditure has been on the rise especially in the developing economies and this has renewed the argument among economists on the validity of Wagner’s law. Whereas for Keynes, the increase is needed to stimulate aggregate demand for economic growth to take place, Wagner opine that public expenditure is a consequence rather than cause of national productivity hence; it plays no role in the growth of an economy. For the West African Economies, which of these economic concepts prevails? This study seeks to determine the validity of these theories in the sixteen countries that make up West African region using a panel analysis. The result reveals that, first, there is a bidirectional effect or relationship between government spending and economic growth in five West African countries, unidirectional causality flowing from government expenditure to economic growth in four countries, while unidirectional causality from economic growth to government expenditure were in two countries. However, there were no causal relationship between government expenditure and economic growth in the remaining five countries in West Africa. Secondly, using different versions of Wagner’s law, we observed that only Goffman version is truly validated in the West African economies given the value of more than one per cent marginal effect of per capita growth on expenditure. Therefore, for the countries that respond to Keynes theory, there is need for appropriate policies with respect to government spending knowing that it affects the level of growth.